Challenges in delivering brand promise – focusing on municipal healthcare organisations. Issue 3 (13th April 2015) - Hytti, Ulla; Kuoppakangas, Päivikki; Suomi, Kati; Chapleo, Chris; Giovanardi, Massimo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate how healthcare professionals understand a new organisational brand and examine the ideas discussed in relation to it within healthcare organisations. Design/methodology/approach – The research is based on a discursive approach that facilitates understanding how the informants perceived a new organisation brand and how that might shape their activities in the enterprise. Findings – The study identified four distinct interpretative repertoires: the organisational brand as an economic solution, the magic wand, the factory and a servant to the customer. The new brand was understood in terms of economic and business-like functions marked by external branding and its signs (logos, etc.). The brand is not communicated to patients or colleagues and the factory metaphor is applied to work practices. Hence, several potential dilemmas arise concerning the brand promise, customer expectations, economic and efficiency gains and the professional values of employees. Research limitations/implications – Adoption of private-sector practices in semi-public or public-sector organisations is common. This study focuses on how private-sector ideas diffuse into the organisations and how they are translated within them. Practical implications – The authors suggest a stronger emphasis on internal branding as a reconciliation to enhance legitimacy, high-quality customer service and staff wellbeing. Originality/value – Theoretically, the unique contribution of the study is drawing upon healthcare branding, dilemma theory and discursive institutionalism in its interpretation. Consequently, it demonstrates how ideas about the brand and public healthcare are translated and communicated in the examined discourses and how those ideas reconstruct understanding and change behaviour within the organisations.